2001
DOI: 10.1155/2001/68024
|View full text |Cite
|
Sign up to set email alerts
|

Development of Dendritic Cells from GM‐CSF-/-Mice invitro: GM‐CSF Enhances Productionand Survival of Cells

Abstract: The production of dendritic cells (DC) from haemopoietic progenitors maintained in long term stroma-dependent cultures (LTC) of spleen or bone marrow (BM) occurs independently of added granulocyte/macrophage colony stimulating factor (GM-CSF). The possibility that cultures depend on endogenous GM-CSF produced in low levels was tested by attempting to generate LTC from spleen and BM of GM-CSF-/-mice. Multiple cultures from GM-CSF-/-and wild type mice were established and compared for cell production. GM-CSF-/-L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 10 publications
(18 reference statements)
1
12
0
Order By: Relevance
“…It is known that the Csf2 −/− mice have ~20% reduction in the overall number of DCs (Kingston et al, 2009; Ni and O’Neill, 2001) and that GM-CSF induces a survival program in DCs protecting them from apoptosis (Chen et al, 2007). To address whether GM-CSF impacted survival of DCs in vivo, we sorted graft-derived DCs from the dLN.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that the Csf2 −/− mice have ~20% reduction in the overall number of DCs (Kingston et al, 2009; Ni and O’Neill, 2001) and that GM-CSF induces a survival program in DCs protecting them from apoptosis (Chen et al, 2007). To address whether GM-CSF impacted survival of DCs in vivo, we sorted graft-derived DCs from the dLN.…”
Section: Resultsmentioning
confidence: 99%
“…Gene expression studies have shown that LTC‐DCs express genes encoding several cell surface molecules expressed by DCs 101 , 102 . LTCs are distinct from other in vitro cultures for DC production in that stromal cells support DC production without addition of exogenous inflammatory cytokines, reflecting the capacity of the spleen stromal cells to support DC hematopoiesis 103 . The continual production of immature myeloid DCs in LTCs led to the hypothesis that hematopoietic stem or progenitor cells are maintained within LTCs 104 , 105 .…”
Section: Extramedullary Sites For Myelopoiesis Of Dcsmentioning
confidence: 99%
“…As BM is formed around birth and contains approximately the same number of CFC at D2 as does spleen, 2 this late development of DC is consistent with evidence that the most common spleen DC subsets, including cDC and pDC, are not endogenous to spleen, but develop instead from BM precursors that migrate through blood to spleen, although this does not explain the late development of L-DC. 19 Two previous studies claimed to identify the presence of CD11c + 'DC' in C57BL/6J and BALB/c mice by D1. 20,21 As both studies defined DC on the basis of CD11c expression only, and not MHC-II expression or functional capacity, it is possible that these cells do not reflect DC, but instead represent DC precursors.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 However, the development of DC within LTC occurs independently of GM-CSF as LTC that produce dendritic-like cells (LTC-DC) can be established from GM-CSFR À/À mice. 19 Flt3-ligand is also essential for the in vivo and in vitro development of conventional (c) DC and plasmacytoid (p) DC. 20,21 As STX3 does not produce either Flt3-ligand or GM-CSF, 22 a role for these cytokines in L-DC production is not supported.…”
mentioning
confidence: 99%